Social-Structural Predictors of Fentanyl Exposure among Street Involved Youth. (2nd January 2022) - Douglas, Sarah; Hayashi, Kanna; Richardson, Lindsey; DeBeck, Kora; Kerr, Thomas
ABSTRACT: ObjectiveThe emergence of synthetic fentanyl has been a main contributor to North America's rising overdose death rates. While increasing attention has been given to drug-related harm among youth, little is known about how social-structural conditions influence their risk of fentanyl exposure. Therefore, we evaluated potential relationships between social-structural conditions and fentanyl exposure among youth who use illicit drugs in Vancouver, BC. Methods: Data were derived from the At-Risk Youth Study (ARYS), a prospective cohort study. The ARYS cohort involves street-involved youth, who use illicit substances in Vancouver, Canada. A multivariable logic regression analysis model was used to identify social factors associated with recent fentanyl exposure as determined through urine drug screening. Results: Overall, 423 participants were included in this analysis, with 380 (38.23%) testing positive for recent fentanyl exposure. In a multivariable relative risk analysis, living in Vancouver's Downtown Eastside in the last six months (RR = 1.16, 95% CI: 1.03-1.32) and daily heroin injection drug use (RR = 1.31, 95% CI: 1.15 − 1.50) were positively associated with fentanyl exposure. As a secondary measure, we found that within the encounters who denied using fentanyl (92.25% of total encounters), 321 (35.05%) still tested positive. Conclusions: We found that youth residing in Vancouver's Downtown Eastside was positively associated with being exposed to fentanyl. Our findings highlight the need to support youth in finding secure housing outside of Vancouver's drug use epicenter to reduce fentanyl exposure.